2012
DOI: 10.1136/bjophthalmol-2011-300169
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, risk factors and management of paediatric diabetic retinopathy: Table 1

Abstract: Diabetic retinopathy (DR), a common complication of both type 1 and type 2 diabetes, is rarely expressed at a level greater than background retinopathy during childhood and adolescence. Epidemiological studies in paediatric diabetic patients together with data from the Diabetes Control and Complications Trial have demonstrated the importance of glycaemic control in delaying or preventing the development of DR; thus, the incidence of DR has declined somewhat over the past two decades. Both prepubertal and postp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 114 publications
1
20
0
2
Order By: Relevance
“…The International Society for Pediatric and Adolescent Diabetes (ISPAD) suggests that annual screening for retinopathy to be conducted in patients aged 11 years after diabetes of 2 years’ duration and from 9 years of age with diabetes of 5 years’ duration [4, 5]. …”
Section: Introductionmentioning
confidence: 99%
“…The International Society for Pediatric and Adolescent Diabetes (ISPAD) suggests that annual screening for retinopathy to be conducted in patients aged 11 years after diabetes of 2 years’ duration and from 9 years of age with diabetes of 5 years’ duration [4, 5]. …”
Section: Introductionmentioning
confidence: 99%
“…5,7,8,10,11,13 The decision on what age to start DR screening will be determined by the mission statement of a DR screening programme. 7,14 If it is to detect STDR, then our data support 12 years of age to be the right age as demonstrated in our population. However, if it is important to identify first detection of development of DR, for example, to review diabetes medical management, then ideally DR screening should start 6 years after the onset of childhood diabetes.…”
Section: Eyementioning
confidence: 99%
“…9 Previous studies have been carried out to assess DR prevalence in young patients. The majority of these studies showed that a small percentage of patients younger than 12 years developed DR. 7,10,11 The main aim of the audit was to assess whether the current starting age is appropriate in relation to identification of STDR. A secondary aim was to determine whether diabetes duration should be taken into account when deciding at what age to start screening for DR in children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retinopatia cukrzycowa (DR) stała się najczęstszą przyczyną ślepoty czy utraty ostrości wzroku u pacjentów w wieku produkcyjnym i jej występowanie wykazuje na ciągły wzrost [3][4]. Zmiany na dnie oka jawne klinicznie występują również u młodych pacjentów z T1DM [5][6]. W badaniach z Oxford Regional Prospective Study (ORPS) wykazano, że u dzieci i młodzieży z T1DM częstość późnych powikłań naczyniowych była wyższa niż u dorosłych po podobnym czasie trwania cukrzycy oraz z porównywalnymi średni-mi poziomami glikemii [6].…”
Section: Wstępunclassified